Quarantine Stressing Voluntary Compliance - DiGiovanni, Cleto (Centers for Disease Control and Prevention, 2005)
A 1-day table-top exercise in San Diego, California, in December 2004 emphasized voluntary compliance with home quarantine to control an emerging infectious disease outbreak. The exercise heightened local civilian-military collaboration in public health emergency management. Addressing concerns about lost income by residents in quarantine was particularly challenging.